Comparison of fibulin-3 and mesothelin as markers in malignant mesothelioma - Creaney, Jenette (BMJ Publishing Group, 2014)
BACKGROUND: Pleural malignant mesothelioma (MM) is a deadly tumour predominantly associated with asbestos exposure. A reliable diagnostic and prognostic marker for MM will significantly enhance clinical care and is an area of intense research. Soluble mesothelin is the most studied and an FDA-approved biomarker for MM. A recent report showed promising results using fibulin-3 as a new diagnostic marker. The aim of this study was to compare the utility of fibulin-3 versus mesothelin, singly or in combination. METHODS: Fibulin-3 and soluble mesothelin were determined by ELISA in the plasma and pleural fluid of 153 patients presenting with a pleural effusion including 82 with MM, 36 with non-MM malignant effusions and 35 with benign effusions. Biomarker concentrations were determined in the plasma of an additional 49 cases with benign asbestos-related disease. RESULTS: Mesothelin provides better diagnostic accuracy than fibulin-3 for MM whether measured in plasma or pleural effusion: area under the curve (AUC) for plasma was 0.822 (95% CI 0.76 to 0.87) compared with 0.671 (0.61 to 0.73), respectively, and for pleural fluid AUC was 0.815 (0.74 to 0.87) compared with 0.588 (0.51 to 0.67), respectively. Effusion fibulin-3 was an independent significant prognostic factor for survival in MM patients; HR 2.08 (1.14 to 3.82), p=0.017. MM patients with effusion fibulin-3 levels below the median survived significantly longer than those with levels above the median (14.1 vs 7.9 months, p=0.012). Mesothelin and neutrophil to lymphocyte ratio were not significant prognostic markers. CONCLUSIONS: Soluble mesothelin is a superior diagnostic biomarker for MM compared with fibulin-3, whereas fibulin-3 provides superior prognostic information compared with mesothelin.